DISTRIBUSI DAN KELIMPAHAN SEMAIAN Rhizophora PADA ZONA INTERTIDAL DI EKOSISTEM MANGROVE DESA JAGO-JAGO KABUPATEN TAPANULI TENGAH - Reynhard '; Khairijon '; Mayta Novaliza Isda (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This research was conducted from April until May 2013, and aimed to identify and analyze the distribution and abundance of Rhizophora seedlings in the intertidal zone of mangrove ecosystem in Jago-jago Village. The observed parameters were distribution, abundance, and water and soil quality. The observation of seedling sample at front, middle, and back of the intertidal zone were systematically conducted using a transect method, where each transect consisted of four plots (4m x 4m in size). The result found two Rhizophora species, namely R. apiculata and R. mucronata that have grown in environments with ideal conditions of temperature, salinity, and pH. The highest abundance of Rhizophora seedlings (11406,25 ind/ha) was found in the middle of intertidal zone. The distribution of Rhizophora seedlings at Jago Jago Village according to morisita index is uniform (Ip< 0).